Universal independence income: A EUROMOD utopian simulation in the UK - Franco Bonomi Bezzo (University of Essex, Institute for Social and Economic Research (ISER), 2021)
In this paper we want to provide an utopian attempt to tackle inequality and to tackle, most specifically, what we consider the cultural and ethical origin of inequality: paid work. We believe that a globalised world, structured around the asymmetry between an increasingly small number of employers and an increasing, almost unlimited, supply of always available employees, leads to increasing inequalities. Under our perspective, in the post-industrialised economies of all major developed countries, paid work cannot be seen anymore as an instrument of self-determination (Marx, 1844) but becomes the main generator of exploitation and poverty. For this reason, we try to develop a benefit with attached strong disincentives to paid work that should provide people with an exit strategy and higher bargaining power. After presenting the main typologies of income benefits that are normally in use or discussed we provide a theoretical explanation of the Universal Independence Income (UII) benefit we want to introduce. We simulate the introduction of our preferred version of UII, two variations of UII and five forms of Universal Basic Income (UBI) to be compared with the tax and benefit system currently in place in the UK. Our main findings suggest that UII has a positive effect on inequality an almost null effect on poverty and strong positive effects on work disincentives.
Keywords: D31; H21; H23; I38; 330; post-work; UBI; inequality; redistribution; United Kingdom